Middle Ear Paraganglioma: Diagnostic Challenges and Surgical Management - A Case Report - Savitskaya, Tatyana; Kutaj, Aleksandra; Savitski, Kiryl; Błaszczyk, Wiktoria; Wiczkowski, Dawid; Łapa, Wiktor; Pikenina, Daria (Quality in Sport, 2025)
Introduction and Purpose. Middle ear paraganglioma (glomus tympanicum) is a rare, benign, highly vascular neuroendocrine tumor arising on the cochlear promontory. Despite its benign nature, it may cause local destruction and symptoms such as pulsatile tinnitus, conductive hearing loss, or a retrotympanic mass. Computed tomography (CT) and magnetic resonance imaging (MRI) are essential for diagnosis. The aim of this study is to present a clinical case and underline the role of imaging, embolization, and surgery. Materials and Methods. A single case was analyzed, including clinical data, otoscopic findings, CT, angiography, details of embolization and surgery, and histopathological results. High-resolution CT was used to assess bony involvement, while angiography defined vascular supply and enabled preoperative embolization. The tumor was surgically removed, and histopathology confirmed paraganglioma. Results. The patient presented with pulsatile tinnitus, progressive hearing loss, and intermittent otorrhea. Otoscopy revealed a pink, pulsatile mass within the external auditory canal. CT showed a well-defined with limited bony erosion. Angiography demonstrated marked vascularity arising from branches of the middle meningeal artery. Embolization effectively reduced tumor perfusion. The mass was completely removed surgically, requiring resection of a diseased incus and reconstruction of the middle ear. Recovery was uneventful. Conclusion. Middle ear paraganglioma should be considered in patients with pulsatile tinnitus and vascular retrotympanic masses. CT and MRI are essential for evaluating lesion extent, while angiography and embolization reduce intraoperative bleeding and facilitate safer surgery. Surgical excision remains the treatment of choice for class A/B tumors. The present case supports the effectiveness of a multistep approach incorporating imaging, vascular control, and precise surgical technique.